Analysis of Resident Satisfaction with Public Facilities and Building Physical Conditions Using the Importance Performance Analysis (IPA) Method (Case Study: Green Semanggi Mangrove Housing Estate): Analisis Kepuasan Penghuni terhadap Fasilitas Umum dan Kondisi Fisik Bangunan Menggunakan Metode Importance Performance Analysis (IPA) (Studi Kasus Perumahan Green Semanggi Mangrove) - rizki Apriliani; Wisnu Abiarto; Andreas Septian Danuwarta (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
The demand for adequate housing in Indonesia continues to increase along with population growth and changes in community lifestyles. However, the provision of housing infrastructure and facilities still faces various challenges that affect housing quality. This study aims to analyze residents’ satisfaction with building physical conditions and public facilities in Green Semanggi Mangrove Housing using the Importance–Performance Analysis (IPA) method. The data were collected through a Likert-scale questionnaire distributed to 106 respondents. The results indicate that the average level of conformity between performance and importance reached 84.05%, suggesting that, in general, the condition of facilities and buildings has fairly met residents’ expectations. Nevertheless, several attributes still require special attention. Based on the Cartesian diagram analysis, in-house sanitation, including the functionality of toilets and sinks as well as the absence of unpleasant odors, falls into the main priority quadrant. This finding indicates a gap between the level of importance and performance for this attribute. Therefore, improvements are necessary through enhancing ventilation systems, repairing plumbing and drainage installations, installing standard water traps, and conducting routine maintenance to improve comfort and ensure the sustainability of housing quality. Keywords: building physical condition, public housing facilities, importance performance analysis (IPA)